1995
DOI: 10.1111/j.1365-2591.1995.tb00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulpotomy of carious vital teeth with periapical involvement

Abstract: Twenty-six permanent vital molars with carious pulp exposures and periapical involvement presenting as radiolucencies or radiopacities on radiographic examination, in patients aged between 10-24 years, were treated using an atraumatic surgical technique with calcium hydroxide alone. The healing was evaluated using clinical and radiographic criteria: absence of clinical symptoms, sensitivity of the radicular pulp, formation of a hard tissue barrier in the exposed area, resolution of periapical involvement and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 24 publications
1
74
0
Order By: Relevance
“…Second, the study methodologies of each treatment were different in terms of case selection, material used, and treatment protocol. For example, teeth with a history of spontaneous pain with periapical radiolucency lesion were included in full pulpotomy (19,20) and partial pulpotomy studies (18,26) but not in direct pulp capping studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the study methodologies of each treatment were different in terms of case selection, material used, and treatment protocol. For example, teeth with a history of spontaneous pain with periapical radiolucency lesion were included in full pulpotomy (19,20) and partial pulpotomy studies (18,26) but not in direct pulp capping studies.…”
Section: Discussionmentioning
confidence: 99%
“…The vitality test, for example, thermal test or electric pulp test, reveals only a yes or no response (13,16). Currently, several studies have reported successful outcome of vital pulp therapy in vital teeth with cariously exposed pulp with signs and symptoms of irreversible pulpitis with periapical lesions (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…However, many recent pulpotomy studies have reported success in this area utilizing both CH (Mejare & Cvek 1993;Caliskan 1995) and MTA (Witherspoon et al 2006;Eghbal et al 2009). In a clinical case reported in 2001, Schmitt et al submitted the first published case of the use of MTA in a symptomatic permanent tooth diagnosed with reversible pulpitis and exhibiting open apices.…”
Section: Symptomatic Permanent Teethmentioning
confidence: 99%
“…are evident unless there is also periapical involvement presenting as a radiolucency or radiopacity. 25 Sometimes, the gingival tissues may grow into the carious lesion and this may be suggestive of a hyperplasic pulpitis (Fig 8b). In these cases the distinction may be made by careful examination of the tissue mass, so as to determine if it is connected to the pulp or to the gingivae.…”
Section: Hyperplasiamentioning
confidence: 99%